Implementasi Sistem Perhitungan Jumlah Penumpang dalam Halte Transjakarta berbasis Wireless Sensor Network - Aditya Hertian; Mochammad Hannats Hanafi Ichsan; Agung Setia Budi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Public transportation is very popular with many people, one of which is the busway or bus rapid transit. However, due to the large number of public transport users and also the limited transportation fleet, public transport passengers are jostled, especially during rush hours. Especially with the Covid-19 pandemic, public transportation has become a vulnerable place for the spread of the virus. To prevent the spread of the virus as well as unwanted things, public transport service providers make policies by limiting the number of passengers. However, it is still not effective, therefore a wireless sensor network- based system was created to calculate the maximum number of passengers who boarded one bus. By tapping the passenger counter module and the module will send the number of passengers to the passenger monitoring system using the MQTT communication protocol. It takes between 0.5-1.5 seconds for the passenger counter module to calculate and send data to the passenger monitoring system with the MQTT communication protocol